ZnS@BSA Nanoclusters Potentiate Efficacy of Cancer Immunotherapy. Issue 49 (7th October 2021) - Cen, Dong; Ge, Qiwei; Xie, Congkun; Zheng, Qiang; Guo, Jiansheng; Zhang, Yuqi; Wang, Yifan; Li, Xiang; Gu, Zhen; Cai, Xiujun
Abstract: Although immunotherapy such as immune checkpoint inhibitors has shown promising efficacy in cancer treatment, the responsiveness among patients is relatively limited. Activation of the cyclic guanosine monophosphate‐adenosine monophosphate synthase/interferon gene stimulator (cGAS/STING) signaling pathway to upregulate innate immunity has become an emerging strategy for enhancing tumor immunotherapy. Herein, ZnS@BSA (bovine serum albumin) nanoclusters synthesized via a self‐assembly approach are reported, where the released zinc ions under acidic tumor microenvironment significantly enhance cGAS/STING signals. Meanwhile, intracellular zinc ions can produce reactive oxygen species, which is further facilitated by the generated H2 S gas from ZnS@BSA via specifically inhibiting catalase in hepatocellular carcinoma cells. It is found that the nanoclusters activate the cGAS/STING signals in mice, which promotes the infiltration of CD8 + T cells at the tumor site and cross‐presentation of dendritic cells, leading to an improved immunotherapy efficacy against hepatocellular carcinoma. Abstract : ZnS@BSA (bovine serum albumin) nanoclusters can promote reactive oxygen species accumulation and activate cyclic guanosine monophosphate–adenosine monophosphate synthase/interferon gene stimulator signals in hepatocellular carcinoma (HCC), further suppressing tumor growth with more immune cells infiltration, which can serve as a new strategy for immunotherapy of HCC.